OP05 Visualising infection with optimised light for education and training (violet). (July 2018) - Poller, Bozena; Hall, Sam; Bailey, Claire; Gregory, Samantha; Clark, Richard; Roberts, Paul; Tonbridge, Anne; Poran, Vin; Crook, Brian; Evans, Cariad
Abstract : Aim: Complex personal protective equipment (PPE) is used by healthcare workers (HCWs) whilst caring for patients with suspected high consequence infectious diseases (HCIDs) such as Ebola. Training in its correct removal is vital to prevent cross-contamination, yet standardised methods for this and assessment of user competency have been lacking. To address this, an evidence-based PPE assessment and training tool was developed in a collaborative project between the Health and Safety Executive research laboratory and Sheffield Teaching Hospitals Foundation Trust, resulting in the creation of VIOLET: Visualising Infection with Optimised Light for Education and Training. Objectives: Using the experience of the British Ministry of Defence's training of staff deploying to West Africa during the Ebola Virus Disease outbreak, 1 a UV fluorescence-based simulation exercise was created and tailored to the needs of UK health workers. Summary of work undertaken: A healthcare mannequin was adapted to transmit different simulated bodily fluids (vomit, diarrhoea, sweat, cough and blood), each with a different coloured UV-fluorescent tracer. PPE-trained HCWs participate in an immersive simulation exercise, performing a clinical assessment of the 'patient' and completing tasks, during which they become exposed to the bodily fluids. Participants are then screened under UV light both before and after doffing PPE, with any contamination photographed for further analysis. Mechanisms of contamination are discussed with the participants real-time, with correction of any steps in doffing where needed. The exercise is also observed by trainers to identify potential latent errors within the simulation. 2 References: . Clay KA, O'Shea MK, Fletcher T, Moore AJ, Burns DS, Craig D, et al. Use of an ultraviolet tracer in simulation training for the clinical management of Ebola virus disease. J Hosp Infect2015;91:275e7. . Poller B, Hall S, Bailey C, Gregory S, Clark R, Roberts P, et al. 'Violet' e a fluorescence-based simulation exercise for training healthcare workers in the use of personal protective equipment. J Hosp Infect2018;99:229–35.